Integrated navigation system for indoor service robots in large-scale environments - Chung, W; Kim, G; Kim, M; Lee, C (2004 IEEE INTERNATIONAL CONFERENCE ON ROBOTICS AND AUTOMATION, VOLS 1- 5, PROCEEDINGS, 2004)
This paper describes an integrated navigation strategy for the autonomous service robot in large-scale indoor environments. It includes architecture of navigation system, the development of crucial navigation algorithms like map, path planning, and localization, and planning scheme such as error/fault handling. Major advantages of proposed navigation are as follows: 1) A range sensor based generalized scheme of navigation without modification of the environment 2) Intelligent navigation-related components. 3) Framework supporting the selection of multiple behaviors and error/fault handling schemes. A experimental result shows the feasibility of proposed navigation system. The result of this research has been successfully applied to our three service robots in a variety of task domains including a delivery, a patrol, a guide, and a floor cleaning task.